2009
DOI: 10.1002/path.2592
|View full text |Cite
|
Sign up to set email alerts
|

Non‐structural 5A protein of hepatitis C virus induces a range of liver pathology in transgenic mice

Abstract: Hepatitis C virus (HCV) is a major cause of chronic hepatitis, liver cirrhosis and hepatocellular carcinoma (HCC). However, the mechanism of HCV pathogenesis is not well understood. Our previous in vitro studies suggested that non-structural 5A (NS5A) protein may play an important role in liver pathogenesis. To elucidate the mechanism of HCV-induced liver pathogenesis, we investigated the histopathological changes of liver in transgenic mice harbouring the NS5A gene. We generated transgenic mice harbouring HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 41 publications
6
50
0
Order By: Relevance
“…7 to 9). In line with our observations, the NS5A-mediated induction of ROS production (68) and JNK activation (49) was reported previously by other investigators.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…7 to 9). In line with our observations, the NS5A-mediated induction of ROS production (68) and JNK activation (49) was reported previously by other investigators.…”
Section: Discussionsupporting
confidence: 81%
“…Recently reported data suggest that ROS production is induced in NS5A-expressing cells (17) or in hepatocytes of NS5A transgenic mice (68). We therefore sough to determine whether NS5A contributes to increased hepatic gluconeogenesis through the induction of ROS production.…”
Section: Vol 85 2011mentioning
confidence: 99%
“…We along with other groups previously reported that HCV NS5A protein is involved in mitochondrial reactive oxygen species (ROS) production (11,13,38). Mitochondrial ROS generation is known to induce the autophagy pathway (22) and lysosomal membrane permeabilization (8).…”
Section: Discussionmentioning
confidence: 99%
“…Histopathology of chronic hepatitis C underscores the contribution of the immune system in the defense against the virus, whereby it contributes to formation of lymphoid follicles in portal tracts as well as abundant lymphocytic infiltrates and a high degree of mesenchymal reaction in the sinusoids [11] . Although some reports on transgenic mice containing virus genomic segments, as the core suggests a cytopathic effect with fatty metamorphosis of hepatocytes [12] , data from animal experiments and clinical observation give solid evidence that the liver damage is induced by the immune defense of the organism against the virus with innate basic immune mechanisms and a subsequent rigorous adaptive immune response [13] .…”
Section: Hepatitis Bmentioning
confidence: 99%